Pengaruh motivasi dan disiplin kerjaterhadap kinerja guru dan pegawai pada Sekolah Dasar Negeri 149/IV Kota Jambi - Suryani, Suci Novi; Rosita, Sry; Kurniawan, Dwi (Jurnal Dinamika Manajemen, 2021)
This study aims to analyze the effect of motivation and work discipline on the performance of teachers and employees at SDN No. 149 / IV Jambi City. The population in this study were all teachers and employees, amounting to 31 people. Data collection was carried out by distributing questionnaires with survey techniques. Data analysis uses descriptive and quantitative methods, namely multiple linear regression analysis using the SPSS program. The study results indicate that the variables of motivation, work discipline, and performance have been carried out well according to the respondents' answers which produce a high average or agree. The multiple linear regression test results show that the motivation variable (X1) and work discipline (X2) have a positive and significant effect both partially and simultaneously on the performance of teachers and employees (Y) at SDN Number 149 / IV Jambi City.